Applying the Optimized CO Rebreathing Method for Measuring Blood Volumes and Hemoglobin Mass in Heart Failure Patients - Ahlgrim, Christoph; Birkner, Philipp; Seiler, Florian; Grundmann, Sebastian; Baumstark, Manfred W.; Bode, Christoph; Pottgiesser, Torben (Frontiers in Physiology, 2018)
Introduction: Determination of blood volume, red cell volume, and plasma volume contributes to the understanding of the pathophysiology in heart failure, especially concerning anemia and volume load. The optimized carbon monoxide (CO)-rebreathing method (oCORM) is used to determine these parameters and hemoglobin mass (Hbmass) in exercise physiology. The applicability of oCORM to determine the intravascular volumes and Hbmass in heart failure patients is currently undetermined because assumptions concerning CO kinetics with oCORM rely on healthy subjects with a normal ejection fraction. Therefore, the aim of the present study is to determine the applicability and the systematic error of oCORM arising from a reduced EF when oCORM is used for measurement of intravascular volumes and Hbmass in heart failure patients. Methods: oCORM was performed in 21 patients with heart failure and a reduced ejection fraction (EF) of < 30% (EFsev) and 25 controls (CONT). CO kinetics in capillary blood was studied 3–15 min after commencement of CO rebreathing. Differences in CO kinetics between the groups were assessed using a generalized linear model. The systematic error for determination of Hbmass with oCORM arising from differences in CO kinetics was assessed using the Monte Carlo method. Results: The CO kinetics was significantly different between EFsev and CONT. In both groups, exposure to CO led to a COHb increase to 6.0 ± 1.0% 3 min after CO rebreathing. There were no CO related side effects or any clinical symptoms. Monte Carlo simulation quantifies the systematic error for determination of Hbmass arising from an impaired ejection fraction to be −0.88%. Conclusion: Our results indicate an impaired vascular mixing of CO when EF is severely reduced. When Hbmass is determined using the original oCORM protocol in heart failure patients with a reduced EF, the systematic underestimation of about 1% should be considered. However, the error arising from this impaired vascular mixing appears small and clinically negligible. Furthermore, application of oCORM was safe and not related to any side effects resulting from CO exposure. In conclusion, oCORM can be used for assessing intravascular volumes and Hbmass in patients with a reduced EF.